Performance and properties of the first plasmas of Wendelstein 7-X. (18th October 2016) - Klinger, T; Alonso, A; Bozhenkov, S; Burhenn, R; Dinklage, A; Fuchert, G; Geiger, J; Grulke, O; Langenberg, A; Hirsch, M; Kocsis, G; Knauer, J; et al.
Abstract: The optimized, superconducting stellarator Wendelstein 7-X went into operation and delivered first measurement data after 15 years of construction and one year commissioning. Errors in the magnet assembly were confirmend to be small. Plasma operation was started with 5 MW electron cyclotron resonance heating (ECRH) power and five inboard limiters. Core plasma values of T e > 8 keV, T i > 2 keV at line-integrated densities n ≈ 3 ⋅ 10 19   m − 2 were achieved, exceeding the original expectations by about a factor of two. Indications for a core-electron-root were found. The energy confinement times are in line with the international stellarator scaling, despite unfavourable wall conditions, i.e. large areas of metal surfaces and particle sources from the limiter close to the plasma volume. Well controlled shorter hydrogen discharges at higher power (4 MW ECRH power for 1 s) and longer discharges at lower power (0.7 MW ECRH power for 6 s) could be routinely established after proper wall conditioning. The fairly large set of diagnostic systems running in the end of the 10 weeks operation campaign provided first insights into expected and unexpected physics of optimized stellarators.